Investigation of the effects of sodium bicarbonate intake on the lactic acid, heart rates and aerobic performance in elit mountain cyclists - Suna, Gürhan; Işıldak, Kenan; Boyraz, Ömer Cumhur (Progress in Nutrition, 2020)
The aim of this study was to investigate the effects of sodium bicarbonate intake on the lactic acid,heart rate and aerobic performance in elite mountain cyclists. Ten cyclists, who were licensed, participatedin the study between 20 and 23 years of age. In the study, 0,3 g/kg body weight dosage NaHCO3 substancewas given orally by mixing 500 ml fruit juice 2 hours before the test. In order to see the Lactate Acid (LA)levels of the athletes, the ergonomics bicycle ergometer test was applied with the Monark brand 839E modelergometer. According to NaHCO3 intake status, Lactate Measurements, HR, Burnout Time and Distancetraveled were recorded. The data obtained from the lactic acid studied in the study were analyzed by repeatedmeasures ANOVA analysis technique in factorial order. In the determination of the difference between theathletes before and after the test, “in-group Paired t test” was applied. The significance level was evaluatedaccording to “0,05” significance level. There was a statistically significant difference between the two groupsof LA values before and after receiving NaHCO3 (p < 0,05). However, there was a more significant decrease inLA values after NaHCO3 + administration. Comparing the NaHCO3 uptake status of the LA values before andafter taking NaHCO3, no significant difference was found (p > 0,05), immediately after the end of the test and5 minutes after the end of the test (p < 0,05). In the present study, the comparison of HR, Burnout durationand distance data in NaHCO3 intake status showed that the performance after NaHCO3 was more significantand there was a statistically significant difference between the intake (p < 0,05). In conclusion, in our study, itwas tested that lactic acid values of NaHCO3 group in lactic acid values were lower. From this point of view,we can say that the athletes taking NaHCO3 can tolerate lactic acid and perform their performances more.